2021
DOI: 10.1021/acsami.0c22148
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Polymer-Derived Interconnected Fe–Ni Alloy by Carbon Nanotubes as an Advanced Design of Urea Oxidation Catalysts

Abstract: The electrochemical urea oxidation reaction (UOR) is considered as a promising renewable source for harvesting energy from waste. We report a new synthetic design approach to produce an iron−nickel alloy nanocatalyst from a metal−organic polymer (MOP) by a single-step carbonization process at 500 °C, thus forming a core−shell of iron−nickel-coated carbon (C@ FeNi) nanostructures wired by embedded carbon nanotubes (CNTs) (CNT/C@FeNi). Powder X-ray diffraction confirmed the formation of metallic FeNi 3 alloy nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 70 publications
(138 reference statements)
0
52
0
Order By: Relevance
“…103 In addition, a bimetallic FeNi alloyed catalyst anchored on conductive CNTs derived from a metal-organic polymer was proposed by the Schechter group, which exhibits an enhanced pre-oxidation reaction as well as UOR activity compared to the FeNi alloy loaded on carbon, further proving the beneficial role of CNTs in promoting such electrochemical processes via regulating the charge transfer ability. 104 Conductive polymers could also be engaged in optimizing the charge transfer and facilitating the pre-oxidation reaction for the UOR. The Song group indicated that the hierarchical Ni nanostructures grown on polypyrrole/graphene oxide (PPy/GO) could promote the generation of catalytically active NiOOH species owing to the fast charge transfer brought by PPy as well as the large surface area guaranteed by the GO substrate, which leads to obviously enhanced UOR activity compared with the unsupported sample.…”
Section: Construction Of Hierarchical Nanostructuresmentioning
confidence: 99%
“…103 In addition, a bimetallic FeNi alloyed catalyst anchored on conductive CNTs derived from a metal-organic polymer was proposed by the Schechter group, which exhibits an enhanced pre-oxidation reaction as well as UOR activity compared to the FeNi alloy loaded on carbon, further proving the beneficial role of CNTs in promoting such electrochemical processes via regulating the charge transfer ability. 104 Conductive polymers could also be engaged in optimizing the charge transfer and facilitating the pre-oxidation reaction for the UOR. The Song group indicated that the hierarchical Ni nanostructures grown on polypyrrole/graphene oxide (PPy/GO) could promote the generation of catalytically active NiOOH species owing to the fast charge transfer brought by PPy as well as the large surface area guaranteed by the GO substrate, which leads to obviously enhanced UOR activity compared with the unsupported sample.…”
Section: Construction Of Hierarchical Nanostructuresmentioning
confidence: 99%
“…In another very recent work, Modak et al used a single‐step carbonization process to convert a metal–organic polymer into core–shell‐type FeNi‐coated carbon nanostructures interconnected by carbon nanotubes (CNT/C@FeNi). [ 97 ] This material was found to be an effective UO catalyst, exhibiting an oxidation current density of 3.5 mA cm −2 at 1.5 V versus RHE. In the absence of CNT, the corresponding material, C@FeNi, displayed a much lower UO current density of 1.1 mA cm −2 .…”
Section: Electrocatalysts For Uomentioning
confidence: 99%
“…Earlier studies have reported the application of bimetallic to be quite noteworthy in contrast to monometallic catalysts. [182][183][184][185] Zhang et al [182] used monometallic (Ni, Ru) and bimetallic NiRu catalyst for the depolymerization of organosolv lignin (130 °C, 1 h). Significantly higher aromatic monomer yields were reported for bimetallic (0.8 wt%) compared to the monometallic (0.16 wt%) catalyst, which further improved for bimetallic catalyst at longer reaction time (Table 10, Entry 5, 6).…”
Section: Reductive Depolymerizationmentioning
confidence: 99%
“…Earlier studies have reported the application of bimetallic to be quite noteworthy in contrast to monometallic catalysts. [ 182–185 ] Zhang et al. [ 182 ] used monometallic (Ni, Ru) and bimetallic NiRu catalyst for the depolymerization of organosolv lignin (130 °C, 1 h).…”
Section: Lignin Valorization Strategiesmentioning
confidence: 99%